ANALISIS PERBEDAAN IMBAL HASIL ANTARA PERUSAHAAN MANUFAKTUR DENGAN PERTAMBANGAN YANG LISTING DI BURSA EFEK INDONESIA - Yandri Rezziansyah Sitompul; Syarief Fauzie (Ekonomi dan Keuangan, 2015)
The purpose of this study was to determine the difference between the yield of a manufacturing company in the field of automotive and mining are listed in the Indonesia Stock Exchange. The data collection techniques used in this research study documentation with data analysis techniques to determine the difference between the yield of a manufacturing company with mining listed in Indonesia Stock Exchange using a different test. The results of this study indicate that the answer to the problem in this research that there is a difference between the yields on the field of automotive manufacturing company with mining listed in Indonesia Stock Exchange. Besides testing different test t test based on table Coefficients known that sig. (2-tailed) and mining stock returns of 0,053 automotive companies which means that the sig. (2-tailed)> 0.05, so it can be said that Ha is accepted, and Ho is rejected which means that there is a difference between the yields on the field of automotive manufacturing company with mines in Indonesian Stock Exchange listingKeyword : Yields, Automotive Company And Mining Company